2022
DOI: 10.2147/cpaa.s345072
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-Like Protein 3 (ANGPTL3) Inhibitors in the Management of Refractory Hypercholesterolemia

Abstract: Cardiovascular disease (CVD) is the most common cause of death in a global scale and significantly depends on the elevated plasma levels of low-density lipoprotein cholesterol (LDL-C) and the subsequent formation of atherosclerotic plaques. While physicians have several LDL-C-lowering agents with diverse mechanisms of action, including statins, ezetimibe, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and inclisiran, angiopoietin-like protein 3 (ANGPTL3) inhibitors have recently emerged as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
2
17
0
2
Order By: Relevance
“…identified 13 different LOF variants of ANGPTL3 , the presence of which was associated with a 41% lower risk of CAD in 13,102 patients with CAD and 40,430 controls. In addition, carriers of the ANGPTL3 LOF variant were found to have 27% lower levels of TG, 9% lower levels of LDL‐C, and 4% lower levels of high‐density lipoprotein cholesterol (HDL‐C) compared with noncarriers 141 . Similar results were reported by Stitziel et al 142 .…”
Section: Drug Development Of Targets Based On Gwas Wgs and Wes Discov...supporting
confidence: 81%
See 3 more Smart Citations
“…identified 13 different LOF variants of ANGPTL3 , the presence of which was associated with a 41% lower risk of CAD in 13,102 patients with CAD and 40,430 controls. In addition, carriers of the ANGPTL3 LOF variant were found to have 27% lower levels of TG, 9% lower levels of LDL‐C, and 4% lower levels of high‐density lipoprotein cholesterol (HDL‐C) compared with noncarriers 141 . Similar results were reported by Stitziel et al 142 .…”
Section: Drug Development Of Targets Based On Gwas Wgs and Wes Discov...supporting
confidence: 81%
“…In addition, carriers of the ANGPTL3 LOF variant were found to have 27% lower levels of TG, 9% lower levels of LDL-C, and 4% lower levels of high-density lipoprotein cholesterol (HDL-C) compared with noncarriers. 141 Similar results were reported by Stitziel et al 142 Musunuru et al 143 found by WES that two mutations (S17X and E129X) in human ANGPTL3 resulted in decreased plasma LDL-C, TG, and HDL-C levels, and also minimized the rate of very low-density lipoprotein (VLDL)-apo B production and increased the rate of LDL-apo B catabolism. Robciuc et al 144 reported that ANGPTL3 LOF carriers exhibit low plasma FFA levels and strong insulin sensitivity.…”
Section: Structure and Function Of Angptl3supporting
confidence: 75%
See 2 more Smart Citations
“…2 A–C). LPL activity is tightly controlled also on a post-transcriptional level, 43 for example by the inhibitor ANGPTL3, which is mainly expressed in the liver, 44 so that the effect of a single C allele might be diminished considerably. In addition, our study may be underpowered to show an additive effect: studies showing an additive effect on lipid levels in the blood included more than 27,000 10 or more than 7,100 18 individuals.…”
Section: Discussionmentioning
confidence: 99%